1986
DOI: 10.1577/1548-8659(1986)6<59:aotdrb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Trip Durations Reported by Marine Sport-Boat Fishermen

Abstract: The Texas Parks and Wildlife Department (TPWD) conducted surveys to determine the accuracy of trip durations reported by marine sport‐boat fishermen. The surveys were conducted at boat ramps on 21 d during May‐August 1982. The fishermen's reported trip duration (nearest 0.5 h) was compared to TPWD's observed trip duration (nearest 0.1 h). No significant differences were found between the reported and observed trip durations by sport‐boat fishermen. Eighty‐six percent of all differences between reported and obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
1
5
1
Order By: Relevance
“…In combination with underreporting of catch, overreporting of time spent angling contributed to the underestimate of mean catch rate and total catch. Edwards (1971) found similar results; however, many other researchers found no significant difference between actual and reported times spent angling or its effect on total catch estimates (Radford 1973;McEachron et al 1986;Phippen and Bergersen 1987;Phippen and Bergersen 1991;Steffe and Murphy 2010). No hypothesis tests were conducted in our study because sampling units were not selected randomly.…”
Section: Modelsupporting
confidence: 70%
See 1 more Smart Citation
“…In combination with underreporting of catch, overreporting of time spent angling contributed to the underestimate of mean catch rate and total catch. Edwards (1971) found similar results; however, many other researchers found no significant difference between actual and reported times spent angling or its effect on total catch estimates (Radford 1973;McEachron et al 1986;Phippen and Bergersen 1987;Phippen and Bergersen 1991;Steffe and Murphy 2010). No hypothesis tests were conducted in our study because sampling units were not selected randomly.…”
Section: Modelsupporting
confidence: 70%
“…Although sample size may have been a limitation, the results of this study are based on the largest sample size of observed anglers in any published study. For instance, Edwards (1971) was based on a sample of 44 anglers, Radford (1973) was based on a sample of 33 angling parties, and McEachron et al (1986) was based on a sample of 94 interviews. The catch rates of Chinook Salmon in Idaho are relatively low compared with other fisheries where self-reporting bias studies have been conducted, which further limits the sample size of observations of successful anglers.…”
Section: Modelmentioning
confidence: 99%
“…In contrast, Johnson and Wroblewski (1962), who instructed their survey clerks to round their observed trip lengths to the nearest quarter hour, found no significant difference between the observed and reported estimates of trip duration. Similarly, McEachron et al (1986) compared anglergenerated estimates (rounded to 0.5 h) to observed trip durations (rounded to 0.1 h) and found no significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of angler-generated estimates of trip duration has been examined in some recreational fisheries (Johnson and Wroblewski 1962;Edwards 1971;Radford 1973;McEachron et al 1986;Phippen and Bergersen 1991). These studies have shown inconsistent trends: some find that anglers tend to overestimate the duration of their fishing trip (Edwards 1971), others that they tend to underestimate it (Phippen and Bergersen 1991), and still others find that angler-generated estimates of trip duration are unbiased (Johnson and Wroblewski 1962;Radford 1973;McEachron et al 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation